Asesmen Pembelajaran di Sekolah Dasar: Kajian Teoritis Prinsip, Teknik, dan Instrumen Penilaian: Abstract, Pendahuluan, Metode, Hasil dan Pembahasan, Kesimpulan, dan Daftar Rujukan - Oktaviandi, Jefri; Isharifa, Atika; Febri Yona Malta , Jingga; Furqon , Mohd; Muhammadi (Journal of Practice Learning and Educational Development, 2026)
This conceptual study explores the theoretical and practical dimensions of learning assessment in elementary education by integrating assessment principles, techniques, and instruments within a unified conceptual framework. Employing a literature review approach, this research synthesizes relevant studies published between 2020 and 2025 from reputable international and national journals to examine current trends and challenges in assessment practices. The findings indicate a significant paradigm shift from traditional product-oriented assessments to formative and authentic assessments that emphasize learning as a reflective and continuous process. Core principles such as validity, reliability, authenticity, and continuity are identified as critical in ensuring fairness, accuracy, and meaningfulness of learning evaluations. Furthermore, the integration of test-based and non-test techniques, alongside the application of digital and authentic instruments, enhances the comprehensiveness and adaptability of assessment implementation in various educational contexts. Despite these advancements, challenges persist in teacher assessment literacy, technological readiness, and the contextual adaptation of assessment practices across diverse school settings. The study concludes by proposing a theoretical model that positions assessment not merely as a tool for measurement but as a pedagogical instrument that fosters reflection, student engagement, and competency-based learning aligned with 21st-century educational goals.